2004
DOI: 10.1080/13577140410001679257
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcoma Protuberans of Scalp With Cervical Lymph Node Metastasis

Abstract: Dermatofibrosarcoma protuberans (DFSP) is an uncommon, slow growing and locally aggressive tumor of the skin with a high rate of recurrence even after supposedly wide excision. The reports of regional lymph node metastasis and distant metastasis are very rare. Because of the extreme rarity of these cases with metastasis, the experience with management of such patients is very limited. A case of recurrent DFSP of scalp, with metastasis to the regional lymph nodes, in a 17-year-old boy is reported here. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Regional lymphatic metastasis is uncommon, approximately 1%, even less frequent than distant metastasis with only a few cases reported in the literature up to date [10,34]. …”
Section: Discussionmentioning
confidence: 99%
“…Regional lymphatic metastasis is uncommon, approximately 1%, even less frequent than distant metastasis with only a few cases reported in the literature up to date [10,34]. …”
Section: Discussionmentioning
confidence: 99%
“…3,4 DFSP grows in an infiltrative manner and has the capacity for local recurrence, though it rarely metastasizes. 5,6 The imaging features of DFSP of the trunk and extremities are nonspecific, including low signal on T1 and high on T2 on MR imaging, with uniform enhancement after contrast administration. 7,8 CT findings include isoattenuated to hypoattenuated lesions without calcifications and uniform (small lesions) to heterogeneous (large lesions) enhancement after contrast administration.…”
mentioning
confidence: 99%
“…Very few such cases are available in literature. [22][23][24][25][26] Various studies have shown synchronous involvement of regional lymph node in patients with STS ranging from 5.9% to 63.15% of cases. In our study, 15.8% (3 of 19) cases showed synchronous involvement.…”
Section: Discussionmentioning
confidence: 99%